Day one postoperative MRI findings following electrode placement for deep brain stimulation: analysis of a large case series - Succop, Benjamin S.; Zamora, Carlos; Roque, Daniel Alberto; Hadar, Eldad; Kessler, Brice; Quinsey, Carolyn (Frontiers in Neurology, 2023)
Objective This study sought to characterize postoperative day one MRI findings in deep brain stimulation (DBS) patients. Methods DBS patients were identified by CPT and had their reviewed by a trained neuroradiologist and neurosurgeon blinded to MR sequence and patient information. The radiographic abnormalities of interest were track microhemorrhage, pneumocephalus, hematomas, and edema, and the occurrence of these findings in compare the detection of these complications between T1/T2 gradient-echo (GRE) and T1/T2 fluid-attenuated inversion recovery (FLAIR) magnetic resonance (MR) sequences was compared. The presence, size, and association of susceptibility artifact with other radiographic abnormalities was also described. Lastly, the association of multiple microelectrode cannula passes with each radiographic finding was evaluated. Ad-hoc investigation evaluated hemisphere-specific associations. Multiple logistic regression with Bonferroni correction (corrected p = 0.006) was used for all analysis. Results Out of 198 DBS patients reviewed, 115 (58%) patients showed entry microhemorrhage; 77 (39%) track microhemorrhage; 44 (22%) edema; 69 (35%) pneumocephalus; and 12 (6%) intracranial hematoma. T2 GRE was better for detecting microhemorrhage (OR = 14.82, p < 0.0001 for entry site and OR = 4.03, p < 0.0001 for track) and pneumocephalus (OR = 11.86, p < 0.0001), while T2 FLAIR was better at detecting edema (OR = 123.6, p < 0.0001). The relatively common findings of microhemorrhage and edema were best visualized by T2 GRE and T2 FLAIR sequences, respectively. More passes intraoperatively was associated with detection of ipsilateral track microhemorrhage (OR = 7.151, p < 0.0001 left; OR = 8.953, p < 0.0001 right). Susceptibility artifact surrounding electrodes possibly interfered with further detection of ipsilateral edema (OR = 4.323, p = 0.0025 left hemisphere only). Discussion Day one postoperative magnetic resonance imaging (MRI) for DBS patients can be used to detect numerous radiographic abnormalities not identifiable on a computed tomographic (CT) scan. For this cohort, multiple stimulating cannula passes intraoperatively was associated with increased microhemorrhage along the electrode track. Further studies should be performed to evaluate the clinical relevance of these observations.